Swinburne and the novel - Krishnan, L (2013)
This study examines Algernon Charles Swinburne’s work as a critic and creator of prose fiction, arguing that it deserves to play a larger role than it has done hitherto in our understanding of him as a writer. It considers a wide range of Swinburne’s prose, situating it in the intellectual movements of his time, and identifying recurrent themes and interests. Finally, it makes a case for a broader view of Swinburne that includes his literary criticism and imaginative prose. The first chapter discusses Swinburne’s prescient criticism of the Brontës and his suggestion that the novel ought to aspire to the status of high art. The second chapter reviews Swinburne’s assessment of Wilkie Collins, which uses the language of the stage to draw comparisons between sensation fiction and drama. Turning to Swinburne’s continental European influences, the third chapter establishes Baudelaire and Hugo as inspirations for Swinburne’s theory of aesthetic practice, though neither directly shaped his serious prose fiction. Gautier’s Mademoiselle de Maupin, which had a much more direct impact through its promotion of sexual and aesthetic autonomy, is discussed in Chapter Four. The fifth chapter studies Boccaccio and The Decameron as a significant source for Swinburne’s proposed Triameron and its surviving short stories. The sixth and seventh chapters focus on Laclos and Balzac, arguably the greatest influences on Swinburne’s novels. Laclos’s epistolary fiction and Balzac’s cycle of interlocking tales are immensely important for Swinburne’s theory of the novel and for his novels themselves. Chapter Eight is an extended study of Swinburne’s novel A Year’s Letters, which displays innovative epistolary form and incisive character studies. Chapter Nine interrogates Lesbia Brandon as a meditation on the youth of a poet and an avant-garde example of Swinburne’s hybrid, poetic prose.